Ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material and preparation method thereof, and pseudocapacitance capacitor
By growing ruthenium nanoparticles in situ on modified cellulose nanofibers and forming a self-supported three-dimensional network structure, the problem of ruthenium dioxide being easily agglomerated and easily shedded is solved, and high-performance electrode materials suitable for portable and wearable electronic devices are prepared.
Patent Information
- Application Number
- CN202411899121.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the industrial preparation of existing ruthenium dioxide as a pseudocapacitor electrode material, there are problems of easy agglomeration and easy to fall off, resulting in unstable materials and difficult to meet the needs of portable and wearable electronic devices.
By growing evenly distributed ruthenium nanoparticles in situ on the modified cellulose nanofibers, a self-supported three-dimensional network structure is formed, and the ruthenium nanoparticles are oxidized by low-temperature annealing to prepare a composite self-supported electrode material of ruthenium dioxide-cellulose nanofibers.
The material overcomes the problem of ruthenium dioxide easy to fall off, has good flexibility and extremely low self-weight, while maintaining excellent specific capacitance and mechanical properties, and is suitable for portable and wearable electronic devices.
Smart Images

Figure HDA0005203003840000011 
Figure HDA0005203003840000012 
Figure HDA0005203003840000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical energy storage, and in particular to a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material and a preparation method thereof, as well as a pseudocapacitor capacitor. Background Art
[0002] With the rise of portable and wearable electronic devices such as medical implants, microsensors, and electronic skin, new demands have been put forward for energy storage devices. Lightweight, flexible, and green energy storage devices with high energy density, high power density, and fast charging and discharging capabilities are key components of portable and mobile electronic products. Compared with secondary batteries, supercapacitors can be used as a substitute or supplement to secondary batteries in applications that require high power output or fast energy collection because of their advantages such as high power density, long cycle stability, and high safety.
[0003] According to the different charge storage mechanisms, supercapacitors can be divided into double-layer capacitors that rely on ion adsorption and pseudocapacitors based on fast surface redox reactions. Pseudocapacitors have both double-layer formation and surface redox reactions, and have higher energy density than double-layer capacitors.
[0004] At present, commonly used pseudocapacitor electrode materials mainly include transition metal oxides, hydroxides, transition metal sulfides, phosphides or conductive polymers. Among them, ruthenium dioxide is recognized as one of the most ideal pseudocapacitor electrode materials because it has metal-like conductivity and good electrochemical stability. However, ruthenium dioxide is expensive and scarce, and its shortcomings of easy agglomeration and easy falling off limit its application in industrial production. In addition, commercially manufactured ruthenium tantalum capacitors generally adopt the method of casting electrode slurry on metal tantalum foil current collector, such as Chinese patent publications CN 102891013 A, CN106024408, etc., and the capacitors produced thereby are not only hard, but also heavy and large in size, and cannot meet the needs of portable and wearable electronic devices. Summary of the invention
[0005] In view of this, the present invention provides a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material and a preparation method thereof, as well as a pseudocapacitor capacitor. The preparation method of the present invention can overcome the problem that ruthenium dioxide particles are easy to agglomerate and fall off in current industrial preparation, and the prepared electrode material has good flexibility and extremely low deadweight, while ensuring excellent specific capacitance.
[0006] The present invention provides a method for preparing a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material, comprising the following steps:
[0007] A) dispersing nanocellulose in a solvent to obtain a nanofiber dispersion;
[0008] B) dissolving hydrated ruthenium trichloride in a solvent to obtain a ruthenium trichloride solution;
[0009] C) mixing the nanofiber dispersion obtained in step A) with the ruthenium trichloride solution obtained in step B) to obtain a mixed solution;
[0010] D) heating the mixed solution obtained in step C) for reaction, then washing the obtained product, dispersing the washed product in a solvent, filtering, and freeze-drying to obtain a film;
[0011] E) annealing the film obtained in step D) to obtain a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material;
[0012] There is no order restriction for step A) and step B).
[0013] Preferably, the mass ratio of the nanocellulose used in step A) to the hydrated ruthenium trichloride used in step B) is 30:(20-30).
[0014] Preferably, in step C), the mixing is carried out by dropwise adding the nanofiber dispersion obtained in step A) to the ruthenium trichloride solution obtained in step B).
[0015] Preferably, in step C), after the nanofiber dispersion obtained in step A) is completely in contact with the ruthenium trichloride solution obtained in step B), stirring is performed;
[0016] The stirring rate is 300-600 rpm, and the stirring time is 2-4 hours.
[0017] Preferably, in step D), the heating reaction is carried out at a temperature of 80 to 150° C. for a time of 12 to 24 hours.
[0018] Preferably, in step E), the annealing treatment is performed at a temperature of 60 to 160° C. for a time of 2 to 12 hours.
[0019] Preferably, in step E), the annealing is performed in an air atmosphere or an oxygen atmosphere.
[0020] Preferably, in step A), the solvent is water; the ratio of the nanocellulose to the solvent is 30 mg: (30-90) mL;
[0021] In step B), the solvent is water; the usage ratio of the hydrated ruthenium trichloride to the solvent is (20-30) mg: 30 mL.
[0022] The present invention also provides a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material prepared by the preparation method described in the above technical scheme.
[0023] The present invention also provides a pseudocapacitor, wherein the electrode material is the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material described in the above technical solution.
[0024] The ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material provided by the present invention is prepared through a series of steps including in-situ growth of uniformly distributed ruthenium nanoparticles on nanocellulose, vacuum filtration and drying to form a self-supporting three-dimensional network structure, and low-temperature annealing to oxidize the ruthenium nanoparticles. The present invention uses in-situ growth technology to firmly anchor ruthenium dioxide nanoparticles on the surface of modified wood cellulose nanofibers with rich surface groups, overcoming the disadvantage that active substances are easy to fall off; at the same time, the surface modified cellulose nanofibers used have a huge specific surface area and a three-dimensional network structure, and have good matching with ruthenium dioxide, which can fully expose the active sites of ruthenium dioxide, maximize the pseudocapacitive activity of ruthenium dioxide, and exert energy storage performance with low ruthenium loading, overcoming the high cost problem of using ruthenium dioxide as a raw material in the prior art; moreover, the nanocellulose substrate used has a low density and a high aspect ratio, and can be formed into a lightweight, flexible self-supporting material by winding, avoiding the use of adhesives, and effectively reducing the weight of electrode materials and energy storage devices; and it is derived from the most widely existing cellulose in nature, which is cheap and easy to obtain, sustainable, and is an ideal material for the development of green energy storage devices. . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 This is a schematic diagram of the appearance of the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material obtained in Example 1;
[0027] Figure 2 The mechanical properties effect diagram of the products obtained in each embodiment and comparative example;
[0028] Figure 3 TEM image of the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material obtained in Example 1;
[0029] Figure 4 The XRD patterns of the products obtained in the embodiments and comparative examples are as follows;
[0030] Figure 5 The thermogravimetric analysis curves of the products obtained in various embodiments and comparative examples are shown;
[0031] Figure 6 The Raman spectra of the products obtained in the embodiments and comparative examples are shown below;
[0032] Figure 7 The graphs are the specific capacitance test results of the products obtained from various embodiments and comparative examples. DETAILED DESCRIPTION
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0034] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0036] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0037] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 150~450W means that the units of the left endpoint "150" and the right endpoint "450" are both W.
[0038] The present invention provides a method for preparing a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material, comprising the following steps:
[0039] A) dispersing nanocellulose in a solvent to obtain a nanofiber dispersion;
[0040] B) dissolving hydrated ruthenium trichloride in a solvent to obtain a ruthenium trichloride solution;
[0041] C) mixing the nanofiber dispersion obtained in step A) with the ruthenium trichloride solution obtained in step B) to obtain a mixed solution;
[0042] D) heating the mixed solution obtained in step C) for reaction, then washing the obtained product, dispersing the washed product in a solvent, filtering, and freeze-drying to obtain a film;
[0043] E) annealing the film obtained in step D) to obtain a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material;
[0044] There is no order restriction for step A) and step B).
[0045] [About Step A]:
[0046] A) Dispersing nanocellulose in a solvent to obtain a nanofiber dispersion.
[0047] In the present invention, the source of the nanocellulose is not particularly limited, and it can be a commercial product or prepared according to a conventional preparation method in the art, for example, it can be prepared from wood cellulose by a tempo oxidation method.
[0048] In the present invention, the solvent is preferably water, more preferably deionized water.
[0049] In the present invention, the dosage ratio of the nanocellulose to the solvent is preferably 30 mg: (30-90) mL, specifically 30 mg: 30 mL, 30 mg: 40 mL, 30 mg: 50 mL, 30 mg: 60 mL, 30 mg: 70 mL, 30 mg: 80 mL, 30 mg: 90 mL.
[0050] In the present invention, the dispersion method for dispersing nanocellulose in a solvent is preferably ultrasonic dispersion. In the present invention, the power of the ultrasonic dispersion is preferably 150 to 450 W, specifically 150 W, 200 W, 250 W, 300 W, 350 W, 400 W, 450 W. The time of the ultrasonic dispersion is preferably 5 to 20 min, specifically 5 min, 10 min, 15 min, 20 min. After the above ultrasonic dispersion, a uniformly dispersed nanofiber dispersion is obtained.
[0051] [About step B]:
[0052] B) dissolving hydrated ruthenium trichloride in a solvent to obtain a ruthenium trichloride solution.
[0053] In the present invention, the solvent is preferably water, more preferably deionized water.
[0054] In the present invention, the usage ratio of the hydrated ruthenium trichloride to the solvent is preferably (20-30) mg:30 mL, specifically 20 mg:30 mL, 25 mg:30 mL, and 30 mg:30 mL.
[0055] [About Step C]:
[0056] C) mixing the nanofiber dispersion obtained in step A) with the ruthenium trichloride solution obtained in step B) to obtain a mixed solution.
[0057] In the present invention, when the nanofiber dispersion obtained in step A) is mixed with the ruthenium chloride solution obtained in step B), the mass ratio of the surface modified cellulose nanofibers used in step A) to the hydrated ruthenium chloride used in step B) is preferably controlled to be 30: (20-30), specifically 30: 20, 30: 21, 30: 22, 30: 23, 30: 24, 30: 25, 30: 26, 30: 27, 30: 28, 30: 29, 30: 30. The present invention controls the above ratio, which can not only ensure the excellent specific capacitance of the material, but also avoid the aggregation of ruthenium dioxide, maintain the flexibility and extremely low dead weight of the electrode. If the proportion of hydrated ruthenium chloride is too low, the specific capacitance of the material is poor. If the proportion of hydrated ruthenium chloride is too high, it is easy to cause the aggregation of ruthenium dioxide, which not only makes the active surface unable to be effectively exposed, but also destroys the flexibility of the electrode and increases its dead weight.
[0058] In the present invention, the mixing method is preferably: adding the nanofiber dispersion obtained in step A) to the ruthenium chloride solution obtained in step B). Wherein, the dropping is preferably done in multiple batches. The amount of each batch added is preferably 10% to 20% of the total mass of the nanofiber dispersion, specifically 10%, 15%, 20%; after each batch is added, the next batch is added after a certain interval; the interval between the addition of each batch is preferably 2 to 5 minutes, specifically 2 minutes, 3 minutes, 4 minutes, 5 minutes. In the present invention, stirring is accompanied during the above mixing process, and the stirring rate is preferably 300 to 600 rpm, specifically 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm.
[0059] In the present invention, after the nanofiber dispersion obtained in step A) is completely in contact with the ruthenium chloride solution obtained in step B) (for example, after all are added dropwise), stirring is performed. The stirring rate is preferably 300 to 600 rpm, specifically 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm. The stirring time is preferably 2 to 4 hours, specifically 2 hours, 3 hours, 4 hours. After the above treatment, a mixed solution is obtained. The present invention can evenly anchor ruthenium ions on the surface of cellulose nanofibers through the above-mentioned stepwise addition and stirring treatment.
[0060] [About Step D]:
[0061] D) heating the mixed solution obtained in step C) for reaction, then washing the obtained product, dispersing the washed product in a solvent, filtering, and freeze-drying to obtain a film.
[0062] In the present invention, the heating reaction can be carried out in a reactor, that is, after the mixed solution is obtained in step C), it is transferred to a reactor for hydrothermal reaction. In the present invention, the temperature of the heating reaction is preferably 80-150°C, specifically 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C. The time of the heating reaction is preferably 12-24h, specifically 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0063] In the present invention, after the above-mentioned heating reaction, the obtained product is washed. The washing is preferably centrifugal washing. The detergent used for the washing is preferably water, more preferably deionized water.
[0064] In the present invention, after the above washing, the washings are dispersed in a solvent. The solvent is preferably water, more preferably deionized water. After the above dispersion, filtration is performed. The filtration is preferably suction filtration. After suction filtration, the product is retained on the filter material, and then freeze-dried to form a film.
[0065] [About Step E]:
[0066] E) Annealing the film obtained in step D) to obtain a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material.
[0067] In the present invention, the annealing treatment is performed in an air atmosphere or an oxygen atmosphere.
[0068] In the present invention, the temperature of the annealing treatment is preferably 60-160°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, more preferably 150°C. The annealing treatment time is preferably 2-12h, specifically 2h, 4h, 6h, 8h, 10h, more preferably 2h. After the above annealing treatment, a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material is obtained.
[0069] The present invention also provides a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material prepared by the preparation method described in the above technical scheme.
[0070] The present invention also provides a pseudocapacitor, wherein the electrode material is the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material described in the above technical solution.
[0071] In the present invention, the pseudocapacitor is a sandwich structure assembled in the order of ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material, diaphragm and ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material; that is, a symmetrical pseudocapacitor supercapacitor is constructed using ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material. Wherein, the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material is preferably pre-soaked in an electrolyte. The soaking time is preferably 10 to 60 minutes, specifically 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, and more preferably 30 minutes. The diaphragm is preferably a NKK-TF4030 diaphragm. The diaphragm is preferably pre-dripped with an electrolyte. The electrolyte is preferably an H2SO4 electrolyte. The concentration of the electrolyte is preferably 0.5 to 2.0M, specifically 0.5M, 1.0M, 1.5M, 2.0M, and more preferably 1.0M.
[0072] The ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material provided by the present invention is prepared by a series of steps such as in-situ growth of uniformly distributed ruthenium nanoparticles on nanocellulose, vacuum filtration and drying to form a self-supporting three-dimensional network structure, and low-temperature annealing to oxidize the ruthenium nanoparticles. The present invention uses in-situ growth technology to firmly anchor ruthenium dioxide nanoparticles on the surface of modified wood cellulose nanofibers with rich surface groups, thereby overcoming the disadvantage that active substances are easy to fall off; at the same time, the surface modified cellulose nanofibers used have a huge specific surface area and a three-dimensional network structure, and have good matching with ruthenium dioxide, which can fully expose the active sites of ruthenium dioxide and maximize the pseudocapacitive activity of ruthenium dioxide; moreover, the nanocellulose substrate used has a low density and a high aspect ratio, and can be formed into a lightweight, flexible self-supporting material by winding, avoiding the use of adhesives, and effectively reducing the weight of electrode materials and energy storage devices; and it is derived from the most widely existing cellulose in nature, which is cheap and easy to obtain, and has sustainability, and is an ideal material for the development of green energy storage devices.
[0073] The preparation method of the present invention is simple, the reaction conditions are mild, and it is suitable for large-scale production and practical applications. The electrode support material used is cellulose nanofiber, which is cheap and easy to obtain, and the active substance ruthenium dioxide achieves energy storage performance with the lowest loading amount, and the cost of large-scale production is controllable. The active material is firmly loaded in an in-situ form, which solves the problem that ruthenium dioxide particles are easy to agglomerate and fall off in current industrial preparation. The biomass support substrate used has the characteristics of light weight and high strength. The prepared electrode composite material has good flexibility and extremely low dead weight. While improving the specific capacitance, it maintains excellent mechanical properties, which can meet the requirements of portable and wearable electronic devices for energy storage devices.
[0074] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In the following examples and comparative examples, nanocellulose is prepared by using coniferous wood fiber bleached pulp through a tempo oxidation process.
[0075] Example 1
[0076] A) 30 mg of dry weight of nanocellulose was added into 40 mL of deionized water and ultrasonically treated in an ultrasonic mill (300 W, 10 min) to obtain a uniformly dispersed nanofiber dispersion.
[0077] B) 30 mg of hydrated ruthenium trichloride powder was dissolved in 30 mL of deionized water and stirred thoroughly to obtain a uniform ruthenium trichloride aqueous solution.
[0078] C) at a stirring rate of 500 rpm, the nanofiber dispersion obtained in step A) is slowly added dropwise to the ruthenium trichloride aqueous solution obtained in step B) in multiple batches, the amount of each batch added is 10% of the total mass of the nanofiber dispersion, and the interval time between each batch of addition is 5 min; after the addition is completed, stirring is continued at 500 rpm for 2 h to obtain a mixed solution.
[0079] D) The mixed solution obtained in step C) is transferred to a reaction vessel and subjected to hydrothermal reaction at 80° C. for 16 h. The obtained product is then centrifuged and washed. The washed product is then redispersed in deionized water, filtered, and freeze-dried to obtain a film.
[0080] E) Annealing the film at 150° C. for 2 h in an air atmosphere to obtain a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material. The product is mainly composed of ruthenium dioxide and wood cellulose nanofibers, with the mass proportion of ruthenium dioxide being 52.3%.
[0081] test:
[0082] The appearance of the obtained ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material is as follows Figure 1 As shown, it can be seen that it exhibits good flexibility. At the same time, the electrode material has a low density. The experimental results show that its density is 1.2g·cm -3 Mechanical properties such as Figure 2 As shown, at room temperature and 50% humidity, the prepared self-supporting electrode film was repeatedly tested for multiple times, and the average tensile strength was 21 MPa, and the average elongation at break was 1.2%.
[0083] The microstructure of the obtained ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material is as follows Figure 3As shown, it can be seen that it is a three-dimensional network structure, proving that the method of the present invention does not destroy the three-dimensional network structure of nanocellulose, the surface of the nanofiber is densely coated with ruthenium dioxide nanoparticles, and there is no agglomeration of ruthenium dioxide particles, so excellent mechanical properties can be obtained. It can also be seen from the TEM image that the size of the ruthenium oxide particles is 1 to 3nm, and the average distance between the particles is less than 2nm, so that electrons can tunnel and realize the circuit conduction of the electrode.
[0084] The XRD patterns of the obtained ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material are as follows: Figure 4 As shown, the characterization results show that the ruthenium dioxide particles are non-crystalline, and amorphous ruthenium dioxide particles can achieve higher capacitance activity than crystalline ones.
[0085] Example 2
[0086] The process was carried out in accordance with Example 1, except that the amount of hydrated ruthenium chloride powder used in step B) was 20 mg.
[0087] The obtained product is mainly composed of ruthenium dioxide and wood cellulose nanofibers, with the mass proportion of ruthenium dioxide being 33.4%.
[0088] The density of the obtained ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material is 1.09 g cm -3 Mechanical properties such as Figure 2 As shown, the prepared self-supporting electrode film was repeatedly tested at room temperature and 50% humidity, and the average tensile strength was 35 MPa and the average elongation at break was 2.9%.
[0089] Comparative Example 1
[0090] The process was carried out in accordance with Example 1, except that the amount of hydrated ruthenium chloride powder used in step B) was 15 mg.
[0091] The obtained product is mainly composed of ruthenium dioxide and wood cellulose nanofibers, with the mass proportion of ruthenium dioxide being 24.7%.
[0092] Comparative Example 2
[0093] The process was carried out in accordance with Example 1, except that the amount of hydrated ruthenium chloride powder used in step B) was 12 mg.
[0094] The obtained product is mainly composed of ruthenium dioxide and wood cellulose nanofibers, with the mass proportion of ruthenium dioxide being 22.9%.
[0095] Comparative Example 3
[0096] The process was carried out in accordance with Example 1, except that the amount of hydrated ruthenium chloride powder used in step B) was 10 mg.
[0097] The obtained product is mainly composed of ruthenium dioxide and wood cellulose nanofibers, with the mass proportion of ruthenium dioxide being 16.7%.
[0098] Product testing:
[0099] (1) Thermogravimetric analysis
[0100] Thermogravimetric analysis was performed on Examples 1-2, Comparative Examples 1-3, and blank samples without adding hydrated ruthenium trichloride powder. The results are as follows: Figure 5 As shown, from the thermogravimetric curves of each sample, it can be seen that the weight proportion of ruthenium dioxide in the products obtained from Examples 1-2 and Comparative Examples 1-3 is 52.3%, 33.4%, 24.7%, 22.9% and 16.7%, respectively.
[0101] (2) Raman test
[0102] Raman tests were performed on the products obtained in Examples 1-2 and Comparative Examples 1-3, and the results are as follows: Figure 6 As shown in the figure, it can be seen from the Raman characteristic peak that the particles in the obtained sample are ruthenium dioxide, and as the weight percentage of ruthenium dioxide increases, the peak intensity increases.
[0103] (3) Specific capacitance test:
[0104] Preparation of pseudocapacitor capacitor: Ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material was immersed in 1M H2SO4 electrolyte at room temperature for 30 min, and then taken out for use. 1M H2SO4 electrolyte was dripped on the surface of commercially available NKK-TF4030 diaphragm (the amount of dripping was 0.06mL / cm 2 ). The soaked ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material and the separator with the electrolyte added thereto are assembled into a symmetrical sandwich structure pseudocapacitor capacitor.
[0105] Use 1mv·s -1 , 2mv·s -1 、5mv·s -1 、10mv·s -1 、25mv·s -1 、50mv·s -1 、100mv·s -1 and 1000mv·s -1 The capacitor was scanned at a voltage scan rate of , and the test results of each embodiment and comparative example are shown in Figure 7 It can be seen that the specific capacitances of electrodes with ruthenium dioxide weight percentages of 16.7%, 22.9%, 24.7%, 33.4% and 52.3% are 20.7 F·g -1 、39.1F·g -1、57.4F·g -1 , 176.1F·g -1 and 730.6F·g -1 When the voltage sweep rate is changed from 1mv·s -1 Increase to 50mv·s -1 When the weight percentage of ruthenium dioxide is 33.4% and 52.3%, the specific capacitance of the electrode (i.e., the electrode of Example 1-2) is reduced by less than 20%, and the high specific capacitance is still maintained. It can be seen that after the ruthenium dioxide particles are loaded, the surface of the insulating lignocellulose nanofibers gradually forms a conductive electron path, and the electron and ion transmission are carried out through the three-dimensional network interwoven by the lignocellulose nanofibers.
[0106] It can be seen from the above test results that the specific capacitance of the product obtained in Example 1-2 of the present invention reaches 176.1F·g -1 As described above, an excellent specific capacitance effect is maintained; at the same time, compared with the prior art, the product obtained by the present invention has excellent flexibility; and the present invention firmly loads in situ, solving the problem that ruthenium dioxide particles are easy to agglomerate and fall off in current industrial preparation; in addition, it has a lower dead weight and maintains excellent mechanical properties.
[0107] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material, characterized in that: The following steps are involved: A) dispersing nanocellulose in a solvent to obtain a nanofiber dispersion; B) dissolving hydrated ruthenium trichloride in a solvent to obtain a ruthenium trichloride solution; C) mixing the nanofiber dispersion obtained in step A) with the ruthenium trichloride solution obtained in step B) to obtain a mixed solution; D) heating the mixed solution obtained in step C) for reaction, then washing the obtained product, dispersing the washed product in a solvent, filtering, and freeze-drying to obtain a film; E) annealing the film obtained in step D) to obtain a ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material; There is no order restriction for step A) and step B).
2. The preparation method according to claim 1, characterized in that: The mass ratio of the nanocellulose used in step A) to the hydrated ruthenium trichloride used in step B) is 30:(20-30).
3. The preparation method according to claim 1, characterized in that: In step C), the mixing is carried out by dropwise adding the nanofiber dispersion obtained in step A) to the ruthenium trichloride solution obtained in step B).
4. The preparation method according to claim 1, characterized in that: In step C), the nanofiber dispersion obtained in step A) is stirred after being completely contacted with the ruthenium trichloride solution obtained in step B); The stirring rate is 300-600 rpm, and the stirring time is 2-4 hours.
5. The preparation method according to claim 1, characterized in that: In step D), the heating reaction temperature is 80-150° C. and the time is 12-24 hours.
6. The preparation method according to claim 1, characterized in that: In step E), the annealing treatment is carried out at a temperature of 60 to 160° C. and for a time of 2 to 12 hours.
7. The preparation method according to claim 1 or 6, characterized in that: In step E), the annealing is performed in an air atmosphere or an oxygen atmosphere.
8. The preparation method according to claim 1, characterized in that: In step A), the solvent is water; the ratio of the nanocellulose to the solvent is 30 mg: (30-90) mL; In step B), the solvent is water; the usage ratio of the hydrated ruthenium trichloride to the solvent is (20-30) mg: 30 mL.
9. A ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A pseudocapacitor, characterized in that: The electrode material is the ruthenium dioxide-cellulose nanofiber composite self-supporting electrode material as described in claim 9.
Citation Information
Patent Citations
Method for preparing ruthenium dioxide combination electrode for energy storage
CN102891013A
Zinc ion hybrid capacitor based on ruthenium oxide / carbon material composite positive electrode and construction method thereof
CN112466677A
Nano-cellulose-based flexible self-supporting nano-paper electrode material for supercapacitor and preparation method of nano-cellulose-based flexible self-supporting nano-paper electrode material
CN115312327A
Preparation method and application of cobaltosic oxide coated carbon self-supporting negative electrode material
CN118908296A
Nano cellulose-based composite having metal oxide layer and preparation method of thereof
KR1020180090762A